2007
DOI: 10.1097/mao.0b013e3180340a1d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hearing Results of Nitinol SMART Stapes Piston Prosthesis With Conventional Piston Prostheses

Abstract: Results demonstrate that experienced surgeons may achieve comparable results with both prostheses; however, the ease of self-crimping and the tightness of the crimp may provide advantages that may have long-term benefits. The potential issue of nickel allergy is important when considering patients for this prosthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 10 publications
2
45
1
1
Order By: Relevance
“…Differences in measured diameter (as opposed to manufacturer's designated diameter) between studied prostheses and the use of pure-tone averages across a 4-octave range may obscure small differences among prostheses and may account for why some studies identified differences between hearing results between nitinol devices and a control group and other studies did not (3,6). …”
Section: Ab Gap By Frequencymentioning
confidence: 99%
“…Differences in measured diameter (as opposed to manufacturer's designated diameter) between studied prostheses and the use of pure-tone averages across a 4-octave range may obscure small differences among prostheses and may account for why some studies identified differences between hearing results between nitinol devices and a control group and other studies did not (3,6). …”
Section: Ab Gap By Frequencymentioning
confidence: 99%
“…Emphasis has however been placed on post operative ABG closure of within 10dB as a measure of surgical success 26,27 . Going by this, 61.1% success as obtained from this study is comparable to findings from many previous published studies 14,20,22,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…The original piston has previously been shown to have comparable (8,12,17) if not superior (18) audiometric outcomes in comparison with other prostheses. Following our hypothesis that this newer circumferential prosthesis would offer superior sound transmission and hence superior audiometric outcomes over the original piston, together with improved stability, we expected our results to reinforce this theory.…”
Section: Discussionmentioning
confidence: 99%